The mistery of Adam’s dream amongst the early christians (Circe de clásicos y modernos, 2018)
The Genesis story about Adam’s dream was subject of thorough considerations between Jews and Christians. Amongst the last named, there are Gnostic motley speculations in which a high valorization of the Feminine, which helps and dignifies the male, can be appreciated. In the present work some aspects from basic texts about Eastern and Christian traditions with regard to this subject and which allow to recover a great deal of the most original of the Early Christian anthropology are analyzed.
Keywords: Adam; dream; woman; Jews; Gnostics